A comb-shaped amphoteric oil displacement agent and a method for preparing the same

By preparing a comb-shaped amphoteric oil displacement agent with a random hydrophobic comb structure, the shortcomings of existing oil displacement agents in terms of shear resistance, salt resistance, and temperature resistance were overcome, and a highly efficient oil displacement effect was achieved in heterogeneous heavy oil reservoirs.

CN117986453BActive Publication Date: 2026-11-06SHANDONG NUOER BIOLOGICAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410223178.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-28
Publication Date
2026-11-06
Estimated Expiration
2044-02-28

AI Technical Summary

Technical Problem

Existing oil displacement agents are insufficient in terms of shear resistance, salt resistance, and temperature resistance, making it difficult to meet the needs of heterogeneous heavy oil reservoirs.

Method used

A comb-shaped amphoteric oil displacement agent with a random hydrophobic comb structure was prepared by copolymerizing components such as acrylamide monomers, zwitterionic surfactants, and betaine-type surfactants. The molecular structure was optimized through initiation reaction and hydrolysis process to improve shear resistance and temperature and salt resistance.

Benefits of technology

The prepared comb-shaped amphoteric oil displacement agent has high molecular weight and high viscosity, and can exhibit excellent shear resistance, temperature resistance and salt resistance in heterogeneous heavy oil reservoirs, making it suitable for improving oil recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117986453B_ABST
    Figure CN117986453B_ABST
Patent Text Reader

Abstract

This invention provides a comb-shaped amphoteric oil displacement agent and its preparation method, wherein the method includes (1) mixing acrylamide monomers, pH buffer, anti-shear agent, surfactant, chain transfer agent, heat stabilizer, anti-crosslinking agent and pore-forming agent to obtain a mixed solution; the surfactant includes amphoteric surfactant and betaine-type surfactant; wherein the amphoteric surfactant is prepared by reacting diethylaminoethyl methacrylate, 11-bromo-1-undecanol and 2-mercapto-3-pyridinecarboxylic acid; (2) adding a composite initiator to the mixed solution to initiate the reaction, and obtaining a polymerization product after the reaction; (3) adding a hydrolyzing agent and a dispersant to the polymerization product and mixing, and obtaining the comb-shaped amphoteric oil displacement agent after hydrolysis. The comb-shaped amphoteric oil displacement agent of this invention has a random comb-shaped structure and has the characteristics of salt resistance, temperature resistance, shear resistance, and suitability for heterogeneous heavy oil reservoirs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical synthesis technology, and in particular to a comb-shaped amphoteric oil displacement agent and its preparation method. Background Technology

[0002] Currently, many oilfields in China are in a stage of high water cut and high recovery, but the overall recovery rate is low, with many wells producing little. In the 1980s, my country developed chemical flooding tertiary oil recovery technology to improve the recovery rate of crude oil after water flooding. This method specifically refers to extracting crude oil by injecting chemical agents underground.

[0003] The ternary composite flooding mechanism involves adding an oil displacement agent to the injection water, giving it high viscosity and low oil-water interfacial tension. This increases the swept volume, displacing more oil remaining in the reservoir and reducing the saturation of the residual oil. Considering the heterogeneity and heavy oil characteristics of existing reservoir formations, and taking into account both swept volume and oil-water mobility ratio, polymer flooding agents with high molecular weight and high viscosity are required.

[0004] In related technologies, the commonly used oil displacement agent is ionic polyacrylamide. However, this type of oil displacement agent has a narrow applicable pH range, an imbalance of positive and negative charges, and is prone to intramolecular and intermolecular entanglement. In particular, it is insufficient in terms of shear resistance, salt resistance, and temperature resistance in tertiary oil recovery, which is widely used in my country, thus greatly restricting the application of polymer oil displacement agents.

[0005] Therefore, based on the above problems, there is an urgent need to provide a new comb-shaped amphoteric oil displacement agent and its preparation method. Summary of the Invention

[0006] This invention provides a comb-shaped amphoteric oil displacement agent that exhibits good shear resistance, salt and temperature resistance, and is suitable for heterogeneous heavy oil reservoirs.

[0007] In a first aspect, the present invention provides a method for preparing a comb-shaped amphoteric oil displacement agent, the preparation method comprising the following steps:

[0008] (1) Acrylamide monomers, pH buffer, anti-shear agent, surfactant, chain transfer agent, heat stabilizer, anti-crosslinking agent and pore-forming agent are stirred and mixed to obtain a mixed solution; the surfactant includes amphoteric surfactant and betaine surfactant; wherein, the amphoteric surfactant is prepared by reacting diethylaminoethyl methacrylate, 11-bromo-1-undecanol and 2-mercapto-3-pyridinecarboxylic acid;

[0009] (2) A composite initiator is added to the mixed solution to initiate the reaction, and the polymerization product is obtained after the reaction.

[0010] (3) Add hydrolysant and dispersant to the polymerization product and stir to mix. After hydrolysis, the comb-shaped zwitterionic oil displacement agent is obtained.

[0011] Preferably, the preparation method of the zwitterionic surfactant is as follows:

[0012] (11) Diethylaminoethyl methacrylate, 11-bromo-1-undecanol and stabilizer are added to an organic solvent, mixed well, and then a catalyst is added. The reaction is heated to obtain the reaction product. Preferably, the reaction temperature is 45-48℃ and the time is 13-16h.

[0013] (12) The reaction product and 2-mercapto-3-pyridinecarboxylic acid are added to water and mixed, and then a catalyst is added. The reaction is heated to obtain the zwitterionic surfactant. Preferably, the reaction temperature is 55-58℃ and the time is 20-23h.

[0014] Preferably, the stabilizer is at least one of hydroquinone, p-tert-butylcatechol, p-hydroxyanisole, or diphenylamine;

[0015] The catalyst is at least one of potassium iodide, ferric chloride, ferric bromide, copper chloride, or copper bromide.

[0016] Preferably, in step (11), the mass percentage of each reactant is: 15-18% diethylaminoethyl methacrylate, 11-13% 11-bromo-1-undecanol, 68.4-73.7% organic solvent, and 0.3-0.6% stabilizer. The amount of catalyst added in step (11) is 0.7-0.8% of the total mass of the reactants.

[0017] Preferably, in step (12), the mass percentage of each reaction raw material is: 23-25% reaction product, 11.5-12.5% ​​2-mercapto-3-pyridinecarboxylic acid, and 62.5-65.5% deionized water, and the amount of catalyst added in step (12) is 0.4-0.5% of the total mass of the reaction raw materials.

[0018] Preferably, in step (1),

[0019] The acrylamide monomer is at least one of acrylamide, N-phenylacrylamide, methacrylamide, or N-hydroxyethylacrylamide;

[0020] The pH buffer solution is at least one of sodium borate-borate buffer, sodium acetate-acetic acid buffer, ammonium phosphate-phosphate buffer, or sodium citrate-citrate buffer.

[0021] The shear-resistant agent is at least one of N-vinylpyrrolidone, 3,4-vinyldioxypyrrole, 3-phenylpropene, allyl sulfone, or 2-allyl anisole.

[0022] The chain transfer agent is at least one of S-ethyl trifluorothioacetate, S-cyanomethyl-S-dodecyl trithiocarbonate, 2-cyano-2-propyldodecyl trithiocarbonate, S,S-dibenzyl trithiocarbonate and dimethyl trithiocarbonate.

[0023] The betaine-type surfactant is at least one of octanoyl thiobetaine, 3-[N,N-dimethyl,N-octadecyl]ammonium, 2-hydroxypropanesulfonate, tetradecyl sulfobetaine or lauryl dimethyl sulfobetaine;

[0024] The heat stabilizer is at least one of thiourea, N-phenylthiourea, S-phenylthiophenyl sulfone, propylene thiourea, 4-methylaminothiourea or N,N′-dibutylthiourea.

[0025] The anti-crosslinking agent is at least one of sodium formate, ascorbic acid, or isopropanol;

[0026] The pore-forming agent is at least one of ammonium bicarbonate, sodium bicarbonate, or potassium bicarbonate.

[0027] Preferably, in step (1), the mass percentages of each reactant are as follows: acrylamide monomer 25-27%, pH buffer 65.83-70.07%, anti-shear agent 0.2-0.3%, zwitterionic surfactant 2-3%, betaine-type surfactant 1-1.5%, chain transfer agent 0.5-0.7%, heat stabilizer 0.8-1.0%, anti-crosslinking agent 0.3-0.5%, and pore-forming agent 0.13-0.17%.

[0028] Preferably, in step (2), the composite initiator includes a first reducing agent, a first initiator, a metal complexing agent, a second initiator, and a third initiator;

[0029] Wherein, the first reducing agent is at least one of sodium metabisulfite, potassium metabisulfite, sodium thiosulfate, thiourea dioxide, zinc dithionite, or stannous chloride; the first initiator is at least one of lithium peroxide, potassium persulfate, zinc peroxide, ammonium persulfate, or cumene hydroperoxide; the metal complexing agent is at least one of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, dihydroxyethylglycine, diethylenetriaminepentamethylphosphonic acid, or ethylenediaminetetramethylphosphonic acid; the second initiator is at least one of tert-butyl hydroperoxide, dicumene peroxide, or tert-butyl cumene hydroperoxide; and the third initiator is at least one of azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline hydrochloride, 4,4'-azodiphenyl ether, diisopropyl azodicarboxylate, and dibenzyl azodicarboxylate.

[0030] Preferably, in step (2), the mass percentage of each raw material added to the composite initiator relative to the mixed solution is as follows: first reducing agent 0.0013-0.0015%, first initiator 0.0011-0.0012%, metal complexing agent 0.015-0.017%, second initiator 0.0075-0.0079%, and third initiator 0.011-0.012%.

[0031] Preferably, in step (3), the hydrolysant is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or ammonia, and the dispersant is at least one of Span80, Span85, Span60 or Span40.

[0032] More preferably, in step (3), the amount of hydrolysant added accounts for 5.2-7.3% of the mass percentage of the polymerization product, and the amount of dispersant added accounts for 0.4-0.6% of the mass percentage of the polymerization product.

[0033] Preferably, in step (2), the initiation temperature of the reaction is 9-11°C, the reaction temperature is 78-81°C, and the reaction time is 11-13h.

[0034] Preferably, in step (3), the hydrolysis temperature is 78-81°C and the time is 6-7 hours.

[0035] Preferably, in step (2), before adding the composite initiator to initiate the reaction, a step of purging nitrogen into the reaction system to remove oxygen is also included.

[0036] Preferably, in step (2), after the reaction is completed, the reaction product is further subjected to washing and granulation in sequence.

[0037] Preferably, in step (3), after hydrolysis is completed, the hydrolysis product is dried and ground sequentially to obtain the comb-shaped zwitterionic oil displacement agent.

[0038] In a second aspect, the present invention also provides a comb-shaped amphoteric oil displacement agent, which is prepared by any of the preparation methods described in the first aspect above.

[0039] Compared with the prior art, the present invention has at least the following beneficial effects:

[0040] (1) In this invention, an amphoteric surfactant is first prepared by reacting diethylaminoethyl methacrylate, 11-bromo-1-undecanol and 2-mercapto-3-pyridinecarboxylic acid. Compared with traditional amphoteric surfactants, this self-made surfactant has the advantages of both amphoteric and hydrophobic association effects. When copolymerized with monomers such as acrylamide monomers, betaine-type surfactants, anti-shear agents and chain transfer agents, a random hydrophobic comb-shaped copolymer can be obtained. The hydrophobic chains repel each other, improving the regularity of the molecular structure and ensuring that the polymer long chains are not easily coiled. The hydrodynamic radius of the molecular chain rotation is larger, resulting in good salt and temperature resistance. Furthermore, the presence of rigid groups in its molecular structure, combined with the effect of the anti-shear agent, ensures that the polymer molecular chain has excellent anti-shear performance. At the same time, the combination of betaine-type surfactant and self-made amphoteric surfactant ensures that the polymer has hydrophobic association effects, good solubility, and can further improve the temperature and salt resistance of the oil displacement agent.

[0041] (2) The comb-shaped amphoteric oil displacement agent in this invention has a random comb-shaped structure and features high molecular weight, high viscosity, salt resistance, amphotericity, temperature resistance, shear resistance, and suitability for heterogeneous heavy oil reservoirs. Specifically, its viscosity-average relative molecular mass is as high as 25-30 million, relative molecular mass distribution coefficient PDI≤1.3, solid content≥90%, degree of hydrolysis 20-24%, apparent viscosity (clear water)≥76mPa·s, apparent viscosity (salt water)≥20mPa·s, filtration factor≤1.5, water insoluble matter≤0.2%, shear viscosity retention rate≥90%, and thermal stability≥80%. Attached Figure Description

[0042] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0043] Figure 1 This is a flowchart of a method for preparing a comb-shaped amphoteric oil displacement agent provided by the present invention. Detailed Implementation

[0044] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0045] like Figure 1 As shown, this embodiment of the invention provides a method for preparing a comb-shaped amphoteric oil displacement agent, which includes the following steps:

[0046] (1) Acrylamide monomers, pH buffer, anti-shear agent, surfactant, chain transfer agent, heat stabilizer, anti-crosslinking agent and pore-forming agent are stirred and mixed to obtain a mixed solution; the surfactant includes amphoteric surfactant and betaine surfactant; wherein, the amphoteric surfactant is prepared by reacting diethylaminoethyl methacrylate, 11-bromo-1-undecanol and 2-mercapto-3-pyridinecarboxylic acid;

[0047] (2) A composite initiator is added to the mixed solution to initiate the reaction, and the polymerization product is obtained after the reaction.

[0048] (3) Add hydrolysant and dispersant to the polymerization product and stir to mix. After hydrolysis, the comb-shaped zwitterionic oil displacement agent is obtained.

[0049] In this embodiment of the invention, an amphoteric surfactant is first prepared by reacting diethylaminoethyl methacrylate, 11-bromo-1-undecanol, and 2-mercapto-3-pyridinecarboxylic acid. Compared with traditional amphoteric surfactants, this self-made surfactant possesses both the advantages of amphoteric surfactants and hydrophobic association effects. Subsequently, it is copolymerized with acrylamide monomers, betaine-type surfactants, anti-shear agents, and chain transfer agents to obtain a copolymer with a random hydrophobic comb-like structure. The mutual repulsion of its hydrophobic chains improves the regularity of the molecular structure, ensuring that the polymer chains are not easily coiled, resulting in a larger hydrodynamic radius of molecular chain rotation and good salt and temperature resistance. Furthermore, the presence of rigid groups in its molecular structure, combined with the effect of the anti-shear agent, ensures excellent shear resistance of the polymer molecular chains. Simultaneously, the combination of the betaine-type surfactant and the self-made amphoteric surfactant ensures the polymer exhibits hydrophobic association effects, good solubility, and further enhances the temperature and salt resistance of the oil displacement agent.

[0050] According to some preferred embodiments, the preparation method of the zwitterionic surfactant is as follows:

[0051] (11) Diethylaminoethyl methacrylate, 11-bromo-1-undecanol and stabilizer are added to an organic solvent, mixed well, and then a catalyst is added. The reaction is heated to obtain the reaction product. The reaction temperature is 45-48℃ and the time is 13-16h.

[0052] (12) The reaction product and 2-mercapto-3-pyridinecarboxylic acid are added to water and mixed, and then a catalyst is added. The reaction is heated to obtain the zwitterionic surfactant. The reaction temperature is 55-58℃ and the reaction time is 20-23h.

[0053] The self-made zwitterionic surfactant in this embodiment of the invention is prepared through a two-step reaction. During the reaction, the above-mentioned reactive monomers are first added to a reaction vessel equipped with a reflux condenser and stirred until homogeneous. Then, an appropriate amount of catalyst is added to the reaction vessel to promote the reaction. At this point, diethylaminoethyl methacrylate and 11-bromo-1-undecanol can undergo a substitution reaction, resulting in a pale yellow precipitate at the bottom of the reaction vessel. The specific reaction process is as follows:

[0054]

[0055] The reaction product formed in the reactor was then filtered to obtain a pale yellow crystal. The organic solvent on the surface of the crystal was then blotted dry with filter paper, and then dried in an oven at 95-98℃ for 1-1.5 hours to obtain a dry, pale yellow granular reaction product. This product was then further esterified with 2-mercapto-3-pyridinecarboxylic acid, resulting in a reddish-brown precipitate at the bottom of the reactor, which is the zwitterionic surfactant (bromomethacryloyloxyethyl diethyl-2-mercapto-3-pyridinecarboxylic acid undecylammonium methanol). The specific reaction process between the pale yellow crystal and 2-mercapto-3-pyridinecarboxylic acid is as follows:

[0056]

[0057] In this embodiment of the invention, after a reddish-brown precipitate forms in the reaction system, the reaction product is filtered to obtain reddish-brown crystals. Then, the surface moisture of the crystals is first absorbed with filter paper, and then dried in an oven at 102-105°C for 2-2.5 hours to obtain a dry amphoteric surfactant. Meanwhile, considering the hydrophobic nature of this surfactant and its poor solubility in water, in this embodiment of the invention, the prepared amphoteric surfactant particles are mixed with an organic solvent (methanol) at a mass ratio of 1:1 to obtain a deep red viscous liquid, which is a 50% (w / w) amphoteric surfactant solution. This facilitates the polymerization reaction of the amphoteric surfactant with other reactive monomers.

[0058] According to some preferred embodiments, the stabilizer is at least one of hydroquinone, p-tert-butylcatechol, p-hydroxyanisole, or diphenylamine; the catalyst is at least one of potassium iodide, ferric chloride, ferric bromide, copper chloride, or copper bromide; in this embodiment, the addition of a stabilizer can prevent the reaction rate from being too fast and ensure that the reaction occurs uniformly.

[0059] According to some preferred embodiments, in step (11), the mass percentage of each reactant is as follows: diethylaminoethyl methacrylate 15-18% (e.g., 15%, 16%, 17% or 18%), 11-bromo-1-undecanol 11-13% (e.g., 11%, 12% or 13%), organic solvent 68.4-73.7% (e.g., 68.4%, 69%, 70%, 72% or 73.7%), and stabilizer 0.3-0.6% (e.g., 0.3%, 0.4%, 0.5% or 0.6%). The amount of catalyst added in step (11) is 0.7-0.6% of the total mass of the reactants. 8% (e.g., it can be 0.7%, 0.75%, or 0.8%); in step (12), the mass percentage of each reaction raw material is: reaction product 23-25% (e.g., it can be 23%, 24%, or 25%), 2-mercapto-3-pyridinecarboxylic acid 11.5-12.5% ​​(e.g., it can be 11.5%, 11.8%, 12%, or 12.5%), deionized water 62.5-65.5% (e.g., it can be 62.5%, 63%, 64%, or 65.5%), and the amount of catalyst added in step (12) is 0.4-0.5% of the total mass of the reaction raw materials (e.g., it can be 0.4%, 0.45%, or 0.5%).

[0060] In this embodiment of the invention, by controlling the amount and proportion of the above-mentioned reaction raw materials within the above-mentioned range, a new zwitterionic surfactant can be synthesized. Its special structure provides both hydrophobic long chains and cationic charges, thereby enabling the surfactant to have both the properties of hydrophobic associative polymers and the advantages of zwitterions.

[0061] It should be noted that in the embodiments of the present invention, the amount of catalyst added is 0.7-0.8% of the total mass of the reaction raw materials, specifically referring to the proportion of the amount of catalyst added to the total mass of diethylaminoethyl methacrylate, 11-bromo-1-undecanol, organic solvent and stabilizer in step (11).

[0062] According to some preferred embodiments, in step (1), the acrylamide monomer is at least one of acrylamide, N-phenylacrylamide, methacrylamide, or N-hydroxyethylacrylamide; the pH buffer is at least one of sodium borate-borate buffer, sodium acetate-acetic acid buffer, ammonium phosphate-phosphate buffer, or sodium citrate-citric acid buffer; the anti-shear agent is at least one of N-vinylpyrrolidone, 3,4-vinyldioxypyrrole, 3-phenylpropene, allyl sulfone, or 2-allyl anisole; and the chain transfer agent is S-ethyl trifluorothioacetate, S-cyanomethyl-S-dodecyl trithiocarbonate, or 2-cyano-2-propyldecyl triacetate. At least one of dialkyl trithiocarbonate, S,S-dibenzyl trithiocarbonate, and dimethyl trithiocarbonate; the betaine-type surfactant is at least one of octanoyl thiobetaine, 3-[N,N-dimethyl,N-octadecyl]ammonium, 2-hydroxypropanesulfonate, tetradecyl sulfobetaine, or lauryl dimethyl sulfobetaine; the heat stabilizer is at least one of thiourea, N-phenylthiourea, S-phenylthiophenyl sulfone, acryloxythiourea, 4-methylaminothiourea, or N,N′-dibutylthiourea; the anti-crosslinking agent is at least one of sodium formate, ascorbic acid, or isopropanol; and the pore-forming agent is at least one of ammonium bicarbonate, sodium bicarbonate, or potassium bicarbonate.

[0063] In this embodiment of the invention, by using a free radical polymerization reaction of the above-mentioned zwitterionic surfactant with acrylamide monomers, pH buffer, anti-shear agent, betaine-type surfactant, chain transfer agent, heat stabilizer, anti-crosslinking agent, and pore-forming agent, a random hydrophobic comb-shaped polymer colloid can be obtained. In this embodiment, the addition of a betaine-type surfactant provides good chemical and thermal stability, strong hydration ability, and contains an equal number of quaternary ammonium cations and sulfonate ions that are not easily affected by the pH value of the solution. Furthermore, it can be used in combination with zwitterionic surfactants, thus ensuring that the polymer molecules have a hydrophobic association effect and good solubility. Simultaneously, the surfactant provides sulfonic acid groups, which is beneficial for improving the temperature and salt resistance of the polymer oil displacement agent. Furthermore, the anti-shear agent used in this embodiment contains rigid groups such as benzene rings and five-membered heterocycles in its molecular structure, which, when combined with zwitterionic surfactants... The copolymerization of serotonin-type surfactants and betaine-type surfactants can significantly improve the rigidity of the polymer flooding agent's molecular chain, increase its steric hindrance, and enhance the product's shear resistance. The addition of chain transfer agents ensures uniform polymer chain length and narrow molecular weight distribution, and can also replace molecular weight regulators to increase the molecular weight of the polymer flooding agent. Simultaneously, it ensures that zwitterionic surfactants form random comb-shaped blocks within the polymer chain. The addition of heat stabilizers prevents polymer chain breakage during high-temperature hydrolysis, increasing the polymer's molecular weight. Furthermore, the addition of pore-forming agents releases gas during the high-temperature hydrolysis stage, causing the polymer colloid to generate bubbles and improving the solubility of the polymer flooding agent. Finally, the addition of anti-crosslinking agents avoids intermolecular crosslinking that easily occurs during the polymerization of ultra-high molecular weight products, ensuring high molecular weight conditions and further improving the solubility of the polymer flooding agent.

[0064] In this embodiment of the invention, adding an appropriate amount of pH buffer can adjust the pH value of the mixed solution to a suitable range, thereby ensuring a faster reaction rate between the monomers. It should be noted that the pH value of the pH buffer in this embodiment of the invention is 6.6-6.8, and the composition ratio of the pH buffer is: 13-15% weak acid (such as acetic acid), 28-29% conjugate acid salt (such as sodium acetate), and 56-59% deionized water.

[0065] According to some preferred embodiments, in step (1), the mass percentages of each reactant are as follows: acrylamide monomer 25-27% (e.g., 25%, 26%, or 27%), pH buffer 65.83-70.07% (e.g., 65.83%, 66%, 68%, or 70.07%), anti-shear agent 0.2-0.3% (e.g., 0.2%, 0.25%, or 0.3%), and zwitterionic surfactant 2-3% (e.g., 2%, 2.5%, or 3%). The following components are included: 1-1.5% betaine-type surfactant (e.g., 1%, 1.25%, or 1.5%), 0.5-0.7% chain transfer agent (e.g., 0.5%, 0.6%, or 0.7%), 0.8-1.0% heat stabilizer (e.g., 0.8%, 0.9%, or 1.0%), 0.3-0.5% anti-crosslinking agent (e.g., 0.3%, 0.4%, or 0.5%), and 0.13-0.17% pore-forming agent (e.g., 0.13%, 0.15%, or 0.17%).

[0066] The experiments in this embodiment have confirmed that using a composite initiator to initiate a polymerization reaction under certain conditions with appropriate amounts of acrylamide monomers, anti-shear agents, amphoteric surfactants, betaine-type surfactants, chain transfer agents, heat stabilizers, anti-crosslinking agents, and pore-forming agents is beneficial for preparing high-molecular-weight, random comb-shaped amphoteric oil displacement agents with high viscosity, temperature and salt resistance, and shear resistance. Amphoteric surfactants and betaine surfactants complement each other. Insufficient amphoteric surfactants hinder the polymer flooding agent's good temperature and salt resistance, while excessive amphoteric surfactants impair its solubility and cause excessive cross-linking between reactants, leading to poor performance. Appropriate combinations of betaine and amphoteric surfactants enable hydrophobic association in the polymer flooding agent, promoting good temperature and salt resistance, shear resistance, and solubility. However, excessive betaine surfactants compromise the agent's viscosity. Simultaneously, appropriate amounts of anti-shear agents significantly improve the rigidity of the polymer chains and increase steric hindrance, further enhancing the shear resistance. However, excessive anti-shear agents reduce the polymer's molecular weight during the reaction, hindering the formation of long-chain polymer flooding agents.

[0067] According to some preferred embodiments, in step (2), the composite initiator includes a first reducing agent, a first initiator, a metal complexing agent, a second initiator, and a third initiator; wherein, the first reducing agent is at least one of sodium metabisulfite, potassium metabisulfite, sodium thiosulfate, thiourea dioxide, zinc dithionite, or stannous chloride; the first initiator is at least one of lithium peroxide, potassium persulfate, zinc peroxide, ammonium persulfate, or cumene hydroperoxide; the metal complexing agent is at least one of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, dihydroxyethylglycine, diethylenetriaminepentamethylphosphonic acid, or ethylenediaminetetramethylphosphonic acid; the second initiator is at least one of tert-butyl hydroperoxide, dicumene peroxide, or tert-butyl cumene hydroperoxide; and the third initiator is at least one of azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline hydrochloride, 4,4'-azodiphenyl ether, diisopropyl azodicarboxylate, and dibenzyl azodicarboxylate.

[0068] According to some preferred embodiments, in step (2), the percentage by mass of each raw material added to the mixed solution in the composite initiator is as follows: first reducing agent 0.0013-0.0015% (e.g., 0.0013%, 0.0014%, or 0.0015%), first initiator 0.0011-0.0012% (e.g., 0.0011%, 0.00115%, or 0.001%). 2%), metal complexing agent 0.015-0.017% (e.g., 0.015%, 0.016% or 0.017%), second initiator 0.0075-0.0079% (e.g., 0.0075%, 0.0076% or 0.0078%), third initiator 0.011-0.012% (e.g., 0.011%, 0.0115% or 0.012%).

[0069] In this embodiment of the invention, by adding the above-mentioned composite initiators to the mixed solution, it is possible to ensure that the free radicals of each reactant monomer have good polymerization efficiency in all temperature ranges, which is beneficial to forming a high-viscosity, temperature- and salt-resistant, and shear-resistant amphoteric random comb-shaped polymer oil displacement agent.

[0070] According to some preferred embodiments, in step (3), the hydrolysant is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or ammonia water, and the dispersant is at least one of Span80, Span85, Span60 or Span40; in step (3), the amount of hydrolysant added is 5.2-7.3% of the mass percentage of the polymerization product (e.g., 5.2%, 5.5%, 6%, 7% or 7.3%), and the amount of dispersant added is 0.4-0.6% of the mass percentage of the polymerization product (e.g., 0.4%, 0.5% or 0.6%).

[0071] In this embodiment of the invention, a post-hydrolysis process is adopted, that is, the homopolymerization reaction of acrylamide monomers is carried out first, and then an appropriate amount of hydrolyzing agent and dispersant are added for high-temperature hydrolysis. In this way, a polymer oil displacement agent product with good solubility and high molecular weight can be prepared.

[0072] According to some preferred embodiments, in step (2), the initiation temperature of the reaction is 9-11°C (e.g., 9°C, 10°C or 11°C), the reaction temperature is 78-81°C (e.g., 78°C, 79°C, 80°C or 81°C), and the reaction time is 11-13h (e.g., 11h, 12h or 13h); in step (3), the hydrolysis temperature is 78-81°C (e.g., 78°C, 79°C, 80°C or 81°C), and the time is 6-7h (e.g., 6h, 6.5h or 7h).

[0073] According to some preferred embodiments, in step (2), before adding the composite initiator to initiate the reaction, a step of purging nitrogen into the reaction system to remove oxygen is also included; in step (2), after the reaction is completed, a step of washing and granulating the reaction products is also included.

[0074] In this embodiment of the invention, before adding the composite initiator to the mixed solution, nitrogen is first introduced into the reaction system to remove oxygen. Then, the composite initiator is added and the reactor is sealed. The temperature of the reaction system is raised to the initiation temperature. At this time, the monomers in the reaction system begin to undergo free radical polymerization. As the polymerization reaction proceeds, the temperature of the reaction system is gradually raised to 78-81°C and kept constant. The reaction is continued at this temperature for 3-4 hours to ensure that the reaction proceeds fully, thereby obtaining a transparent colloidal polymerization product. Finally, the polymerization product is cooled to 23-25°C, washed with acetone 2-4 times, and the colloid is granulated to obtain a granular polymerization product.

[0075] According to some preferred embodiments, in step (3), after hydrolysis is completed, the hydrolysis products are dried and ground in sequence to obtain the comb-shaped zwitterionic oil displacement agent.

[0076] In this embodiment of the invention, after the polymerization product in step (3) is kept warm and hydrolyzed, the hydrolyzed granules are placed in an oven at 95-98°C and dried for 1.5-2 hours. Then they are ground into fine powder and sieved using a standard sieve of 18-70 mesh. This produces a powdered polymer oil displacement agent with good solubility.

[0077] It should be noted that there are no particular restrictions on the stirring speed in each step of the embodiments of the present invention, as long as the reaction raw materials are mixed evenly. Those skilled in the art can make adaptive adjustments according to the actual situation in the process.

[0078] The present invention also provides a comb-shaped amphoteric oil displacement agent, which is prepared by the preparation method provided in the present invention.

[0079] The polymer oil displacement agent in this embodiment of the invention has a comb-like structure. The steric hindrance between its side chains allows the polymer molecular backbone to unfold better. Furthermore, the hydrophobic chains of the side chains can repel each other, improving the regularity of the molecular structure and ensuring that the long polymer chains are not easily coiled. At the same time, the hydrodynamic radius of the molecular chain rotation is larger. In addition, the presence of rigid groups, sulfonic acid groups and ammonium groups in the molecular chain ensures that the polymer molecular chain has excellent temperature resistance, salt resistance and shear resistance, and also ensures that the polymer has zwitterionic properties.

[0080] Experiments in the embodiments of this invention have confirmed that the polymer flooding agent prepared by this invention has the characteristics of high molecular weight, high viscosity, random comb structure, salt resistance, amphotericity, temperature resistance, shear resistance, and suitability for heterogeneous heavy oil reservoirs. Specifically, its viscosity-average relative molecular mass is 25-30 million, relative molecular mass distribution coefficient (PDI) ≤ 1.3, solid content ≥ 90%, degree of hydrolysis 20-24%, apparent viscosity (clear water) ≥ 76 mPa·s, apparent viscosity (salt water) ≥ 35 mPa·s, filtration factor ≤ 1.5, water-insoluble matter ≤ 0.2%, shear viscosity retention rate ≥ 94%, and thermal stability ≥ 88%.

[0081] To more clearly illustrate the technical solution and advantages of the present invention, the following detailed description of a comb-shaped amphoteric oil displacement agent and its preparation method is provided through several embodiments.

[0082] Example 1:

[0083] (1) Preparation of zwitterionic surfactants:

[0084] (11) Add 159g of diethylaminoethyl methacrylate, 118g of 11-bromo-1-undecanol, 4.5g of stabilizer (p-tert-butylcatechol), and 718.5g of organic solvent (petroleum ether) to a reactor equipped with a reflux condenser. Turn on the stirring and set the speed to 315r / min. After the materials in the system are mixed evenly into a colorless and transparent liquid, add 7.3g of catalyst (ferric bromide) and raise the temperature of the reactor to 46.5℃. React at a constant temperature for 15h. At this time, a light yellow precipitate appears at the bottom of the reactor. Filter the above reactants with a full glass frit filter to remove impurities and obtain light yellow crystals. Use filter paper to absorb the petroleum ether and other liquids on the surface of the crystals and dry them in an oven at a set temperature of 96℃ for 1.2h to obtain dry light yellow particles, which are the reaction products.

[0085] (12) Add 238g of the above reaction product, 119g of 2-mercapto-3-pyridinecarboxylic acid and 643g of deionized water to the reaction vessel, start stirring, set the stirring speed to 315r / min, and after all the materials in the system are fully dissolved into a yellow transparent liquid, add 4.6g of catalyst (ferric bromide) and raise the temperature of the reaction vessel to 57℃, and keep the temperature constant for 21.5h. At this time, a reddish-brown precipitate appears at the bottom of the reaction vessel. Filter the obtained mixed reactants with a full glass frit filter to remove impurities and obtain reddish-brown crystals. Use filter paper to absorb the water and other liquids on the surface of the crystals, and then dry them in an oven at a set value of 103℃ for 2.3h to obtain dry reddish-brown particles, which are amphoteric surfactants.

[0086] Add the zwitterionic surfactant and methanol to the reactor at a mass ratio of 1:1, start stirring, and set the stirring speed to 315 r / min. After mixing evenly, a dark red viscous liquid is obtained, which is the 50% mass concentration zwitterionic surfactant, which is ready for use.

[0087] Preparation of pH buffer solution (sodium acetate-acetic acid buffer) with pH 6.72: Mix 135g acetic acid, 285g sodium acetate and 580g deionized water and set aside.

[0088] Add 256g of acrylamide monomer (acrylamide), 682.6g of the above-mentioned pH buffer solution, 2.4g of shear stabilizer (3,4-vinyldioxypyrrole), 26g of the above-mentioned zwitterionic surfactant, 13g of betaine-type surfactant (tetradecyl sulfobetaine), 5.7g of chain transfer agent (S-cyanomethyl-S-dodecyl trithiocarbonate), 8.6g of heat stabilizer (N,N′-dibutylthiourea), 4.1g of anti-crosslinking agent (ascorbic acid), and 1.6g of porogen (sodium bicarbonate) to the reactor. Start stirring at 315r / min until the system is fully dissolved into a colorless and transparent liquid to obtain a mixed solution. Pour the mixed solution into a reactor with a lid and a polytetrafluoroethylene liner, and control the system temperature at 14℃ with a water bath. Deoxygenate by nitrogen blowing for 36min and set aside for use.

[0089] (2) Add a composite initiator (0.014g first reducing agent (sodium thiosulfate), 0.0115g first initiator (cumene hydroperoxide), 0.16g metal complexing agent (dihydroxyethylglycine), 0.077g second initiator (tert-butyl cumene hydroperoxide), and 0.117g third initiator (dibenzyl azodicarbonate)) to the mixed solution. Seal the reactor and protect it with nitrogen. Under the conditions of initiation temperature of 10℃ and external heat preservation of the reactor, react for 8.3h until the system reaches the highest temperature of 80.5℃. Continue to keep it at the temperature for 3.5h. At this time, the system becomes a transparent colloidal state. Cool down to 24℃, take out the colloidal substance, wash it with acetone 3 times, and then granulate it to obtain the polymerization product.

[0090] (3) Pour the above polymerization reaction product into a stirred tank, add 61g of hydrolysing agent (potassium hydroxide) and 5.1g of dispersant (Span60), start stirring, and stir at a speed of 315r / min. After stirring for 18min, pour it into a reactor with a lid and a polytetrafluoroethylene liner. Seal the reactor, control the water bath temperature at 80.2℃, and keep it warm for 6.3h for hydrolysis. Take out the hydrolyzed product, put it in an oven at 96℃, dry it for 1.7h, and grind it through a standard sieve of 18-70 mesh to obtain white particles, which are the comb-shaped amphoteric oil displacement agent.

[0091] Example 2:

[0092] (1) Preparation of zwitterionic surfactants:

[0093] (11) Add 167g of diethylaminoethyl methacrylate, 130g of 11-bromo-1-undecanol, 3.5g of stabilizer (p-tert-butylcatechol), and 699.5g of organic solvent (styrene) to a reactor equipped with a reflux condenser. Turn on the stirring and set the speed to 330r / min. After the materials in the system are mixed evenly into a colorless and transparent liquid, add 7g of catalyst (ferric bromide) and raise the temperature of the reactor to 46.5℃. React at a constant temperature for 13h. At this time, a light yellow precipitate appears at the bottom of the reactor. Filter the above reactants with a full glass frit filter to remove impurities and obtain light yellow crystals. Use filter paper to absorb the liquid such as petroleum ether on the surface of the crystals and dry them in an oven at a set temperature of 96℃ for 1.5h to obtain dry light yellow particles, which are the reaction products.

[0094] (12) Add 238g of the above reaction product, 119g of 2-mercapto-3-pyridinecarboxylic acid and 643g of deionized water to the reaction vessel, start stirring, and set the stirring speed to 330r / min. After all the materials in the system are fully dissolved into a yellow transparent liquid, add 7g of catalyst (ferric bromide) and raise the temperature of the reaction vessel to 57℃. React at a constant temperature for 20h. At this time, a reddish-brown precipitate appears at the bottom of the reaction vessel. Filter the obtained mixed reactants with a full glass frit filter to remove impurities and obtain reddish-brown crystals. Use filter paper to absorb the water and other liquids on the surface of the crystals and dry them in an oven at a set temperature of 103℃ for 2.5h to obtain dry reddish-brown particles, which are amphoteric surfactants.

[0095] Add the zwitterionic surfactant and methanol to the reactor at a mass ratio of 1:1, start stirring, and set the stirring speed to 330 r / min. After mixing evenly, a dark red viscous liquid is obtained, which is the 50% mass concentration zwitterionic surfactant, which is ready for use.

[0096] Preparation of pH buffer solution (sodium acetate-acetic acid buffer) with pH 6.80: Mix 150g acetic acid, 290g sodium acetate and 560g deionized water and set aside.

[0097] Add 270g of acrylamide monomer (methacrylamide), 665.3g of the above-mentioned pH buffer, 2g of anti-shear agent (N-vinylpyrrolidone), 28g of the above-mentioned zwitterionic surfactant, 15g of betaine-type surfactant (tetradecyl sulfobetaine), 5g of chain transfer agent (2-cyano-2-propyldodecyl trithiocarbonate), 8g of heat stabilizer (S-phenylthiophenyl), 5g of anti-crosslinking agent (ascorbic acid), and 1.7g of porogen (sodium bicarbonate) to the reactor. Start stirring at 315r / min until the system is fully dissolved into a colorless and transparent liquid to obtain a mixed solution. Pour the mixed solution into a reactor with a lid and a polytetrafluoroethylene liner, and control the system temperature at 14℃ with a water bath. Deoxygenate with nitrogen for 38min and set aside for use.

[0098] (2) Add the composite initiator (0.015g first reducing agent (potassium metabisulfite), 0.012g first initiator (cumene hydroperoxide), 0.17g metal complexing agent (diethylenetriaminepentaacetic acid), 0.079g second initiator (tert-butyl cumene hydroperoxide), and 0.12g third initiator (dibenzyl azodicarbonate)) to the mixed solution, seal the reactor, protect it with nitrogen, set the initiation temperature to 10℃, and keep the reactor externally warm for 9 hours until the system reaches the highest temperature of 80.5℃. Continue to keep it warm for 3 hours. At this time, the system becomes a transparent colloidal state. Cool down to 24℃, take out the colloidal substance, wash it twice with acetone, and then granulate it to obtain the polymerization product.

[0099] (3) Pour the above polymerization reaction product into a stirred tank, add 52g of hydrolysing agent (potassium hydroxide) and 6g of dispersant (Span60), start stirring, and stir at a speed of 330r / min. After stirring for 15min, pour it into a reactor with a lid and a polytetrafluoroethylene liner. Seal the reactor, control the water bath temperature at 80.2℃, and keep it warm for 7h for hydrolysis. Take out the hydrolyzed product, put it in an oven at 96℃, dry it for 1.7h, and grind it through a standard sieve of 18-70 mesh to obtain white particles, which are the comb-shaped amphoteric oil displacement agent.

[0100] Example 3

[0101] (1) Preparation of zwitterionic surfactants:

[0102] (11) Add 180g of diethylaminoethyl methacrylate, 110g of 11-bromo-1-undecanol, 6g of stabilizer (p-tert-butylcatechol), and 704g of organic solvent (petroleum ether) to a reactor equipped with a reflux condenser. Turn on the stirring and set the speed to 315r / min. After the materials in the system are mixed evenly into a colorless and transparent liquid, add 8g of catalyst (ferric bromide) and raise the temperature of the reactor to 48℃. React at a constant temperature for 15h. At this time, a light yellow precipitate appears at the bottom of the reactor. Filter the above reactants with a full glass frit filter to remove impurities and obtain light yellow crystals. Use filter paper to absorb the petroleum ether and other liquids on the surface of the crystals and dry them in an oven at a set temperature of 95℃ for 1.2h to obtain dry light yellow particles, which are the reaction products.

[0103] (12) Add 238g of the above reaction product, 119g of 2-mercapto-3-pyridinecarboxylic acid and 643g of deionized water to the reaction vessel, start stirring, and set the stirring speed to 315r / min. After all the materials in the system are fully dissolved into a yellow transparent liquid, add 8g of catalyst (ferric bromide) and raise the temperature of the reaction vessel to 58℃. React at a constant temperature for 21.5h. At this time, a reddish-brown precipitate appears at the bottom of the reaction vessel. Filter the obtained mixed reactants with a full glass frit filter to remove impurities and obtain reddish-brown crystals. Use filter paper to absorb the water and other liquids on the surface of the crystals and dry them in an oven at a set temperature of 102℃ for 2.3h to obtain dry reddish-brown particles, which are amphoteric surfactants.

[0104] Add the zwitterionic surfactant and methanol to the reactor at a mass ratio of 1:1, start stirring, and set the stirring speed to 315 r / min. After mixing evenly, a dark red viscous liquid is obtained, which is the 50% mass concentration zwitterionic surfactant, which is ready for use.

[0105] Preparation of pH buffer solution (sodium acetate-acetic acid buffer) with pH 6.72: Mix 130g acetic acid, 280g sodium acetate and 590g deionized water and set aside.

[0106] Add 260g of acrylamide monomer (methacrylamide), 685.7g of the above pH buffer, 3g of shear stabilizer (3,4-vinyldioxypyrrole), 20g of the above zwitterionic surfactant, 10g of betaine surfactant (lauryl dimethyl sulfobetaine), 7g of chain transfer agent (S-cyanomethyl-S-dodecyl trithiocarbonate), 10g of heat stabilizer (S-phenylthiophenyl), 3g of anti-crosslinking agent (ascorbic acid), and 1.3g of porogen (ammonium bicarbonate) to the reactor. Start stirring at 315r / min until the system is fully dissolved into a colorless and transparent liquid to obtain a mixed solution. Pour the mixed solution into a reactor with a lid and a polytetrafluoroethylene liner, and control the system temperature at 13℃ with a water bath. Deoxygenate with nitrogen for 36min and set aside for use.

[0107] (2) Add a composite initiator (0.013g first reducing agent (sodium thiosulfate), 0.011g first initiator (potassium persulfate), 0.15g metal complexing agent (diethylenetriaminepentaacetic acid), 0.075g second initiator (tert-butyl hydroperoxide), and 0.11g third initiator (dibenzyl azodicarbonate)) to the mixed solution. Seal the reactor and protect it with nitrogen. Under the conditions of initiation temperature of 11℃ and external heat preservation of the reactor, react for 8.3h until the system reaches the highest temperature of 78℃. Continue to keep it at the temperature for 3.5h. At this time, the system becomes a transparent colloidal state. Cool down to 23℃, take out the colloidal substance, wash it with acetone 3 times, and then granulate it to obtain the polymerization product.

[0108] (3) Pour the above polymerization reaction product into a stirred tank, add 72g of hydrolysing agent (potassium hydroxide) and 4g of dispersant (Span80), start stirring, the stirring speed is 315r / min, stir for 18min, then pour it into a reactor with a lid and polytetrafluoroethylene liner, seal the reactor, control the water bath temperature at 78℃, and keep it warm for 6.3h for hydrolysis; take out the hydrolyzed product, put it in an oven at 98℃, dry it for 1.7h, and grind it through a standard sieve of 18-70 mesh to obtain white particles, which are the comb-shaped amphoteric oil displacement agent.

[0109] Example 4

[0110] Example 4 is basically the same as Example 1, except that in step (1), the amount of zwitterionic surfactant added is 15g.

[0111] Example 5

[0112] Example 5 is basically the same as Example 1, except that in step (1), the amount of zwitterionic surfactant added is 35g.

[0113] Example 6

[0114] Example 6 is basically the same as Example 1, except that in step (1), the amount of betaine-type surfactant added is 8g.

[0115] Example 7

[0116] Example 7 is basically the same as Example 1, except that in step (1), the amount of betaine-type surfactant added is 16g.

[0117] Example 8

[0118] Example 8 is basically the same as Example 1, except that in step (1), the amount of anti-shear agent added is 3.5g.

[0119] Example 9

[0120] Example 9 is basically the same as Example 1, except that in step (1), the amount of hydrolysant added is 75g.

[0121] Comparative Example 1

[0122] Comparative Example 1 is basically the same as Example 1, except that: when preparing the zwitterionic surfactant in step (11), no stabilizer (p-tert-butylcatechol) is added.

[0123] Comparative Example 2

[0124] Comparative Example 2 is basically the same as Example 1, except that in step (1), no zwitterionic surfactant is added.

[0125] Comparative Example 3

[0126] Comparative Example 3 is basically the same as Example 1, except that no chain transfer agent is added in step (1).

[0127] Comparative Example 4

[0128] Comparative Example 4 is basically the same as Example 1, except that in step (1), no betaine-type surfactant is added.

[0129] Comparative Example 5

[0130] Comparative Example 5 is basically the same as Example 1, except that the zwitterionic surfactant prepared in step (1) is replaced with the same weight of sulfonated 2-(2-quinolinyl)-1H-indene-1,3(2H)-diketone sodium salt.

[0131] Comparative Example 6

[0132] Comparative Example 6 is basically the same as Example 1, except that no anti-shear agent is added in step (1).

[0133] Comparative Example 7

[0134] Comparative Example 7 is basically the same as Example 1, except that the hydrolysis reaction process in step (3) is removed, that is, the polymerization reaction product in step (2) is directly placed in an oven at 96°C, dried for 1.7 hours, and ground through a standard sieve of 18-70 mesh to obtain white particles, which are the comb-shaped amphoteric oil displacement agent.

[0135] The oil displacement agents prepared in Examples 1 to 9 and Comparative Examples 1 to 7 (hereinafter referred to as samples) were subjected to performance index tests. The specific test methods are as follows, and the test results are shown in Table 1.

[0136] Test of viscosity-average relative molecular mass: The viscosity-average relative molecular mass of the sample was tested according to GB / T 17514-2017 standard;

[0137] Relative Molecular Mass Distribution Coefficient (PDI): Refer to the standard GB / T 16631-2008 General Rules for High Performance Liquid Chromatography. The specific detection method is as follows:

[0138] Test conditions: Polymer Laboratory PL-GPC 50 gel permeation chromatograph, GPC detection system with laser scattering, viscosity and refractive index detectors, three columns (PL-aquagel-60, PL-aquagel-40 and PL-aquagel-30) in series, mobile phase of 0.2 mol / L NaNO3 (containing 0.02% w / v NaN3), flow rate of 1 mL / min, column oven temperature of 40℃, detection cycle of 15 min; narrow distribution PEO was used as standard sample (PDI = 1.06);

[0139] Test method: Weigh 0.1g of the above samples and dilute to 100mL in a volumetric flask with the mobile phase to prepare a sample solution of about 1g / L. Filter the solution using a needle filter membrane with a pore size of 0.2μm and then measure the relative molecular mass distribution coefficient.

[0140] Solid content, degree of hydrolysis, apparent viscosity (salt water with a total mineralization of 19334 mg / L), filtration factor, water-insoluble matter, shear viscosity retention rate, and thermal stability were tested according to the standard "Technical Requirements for Polyacrylamide for Oil Displacement".

[0141] Table 1

[0142]

[0143] As shown in Table 1, compared with the comparative example, the comb-shaped amphoteric oil displacement agent prepared in the embodiments of the present invention has the advantages of high molecular weight, high viscosity, good salt resistance, temperature resistance and shear resistance. Its apparent viscosity is ≥20 mPa·s under the condition of mineralization of 19334 mg / L, the shear viscosity retention rate is ≥90% under the condition of shear rate of 400±20 r / min, the thermal stability is ≥90% at the aging temperature of 75℃ and the aging time of 30 days, and the thermal stability is ≥80% at the aging time of 90 days.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for the preparation of a comb-shaped amphoteric oil-displacing agent, characterized in that, The preparation method includes the following steps: (1) Acrylamide monomers, pH buffer, anti-shear agent, surfactant, chain transfer agent, heat stabilizer, anti-crosslinking agent and pore-forming agent are stirred and mixed to obtain a mixed solution; the surfactant includes amphoteric surfactant and betaine surfactant; wherein the amphoteric surfactant is prepared by reacting diethylaminoethyl methacrylate, 11-bromo-1-undecanol and 2-mercapto-3-pyridinecarboxylic acid; The mass percentages of each reactant are as follows: acrylamide monomers 25-27%, pH buffer 65.83-70.07%, anti-shear agent 0.2-0.3%, amphoteric surfactant 2-3%, betaine surfactant 1-1.5%, chain transfer agent 0.5-0.7%, heat stabilizer 0.8-1.0%, anti-crosslinking agent 0.3-0.5%, and pore-forming agent 0.13-0.17%; The acrylamide monomer is at least one of acrylamide, N-phenylacrylamide, methacrylamide, or N-hydroxyethylacrylamide; The pH buffer solution is at least one of sodium borate-borate buffer, sodium acetate-acetic acid buffer, ammonium phosphate-phosphate buffer, or sodium citrate-citrate buffer. The shear-resistant agent is at least one of N-vinylpyrrolidone, 3,4-vinyldioxypyrrole, 3-phenylpropene, allyl sulfone, or 2-allyl anisole. The chain transfer agent is at least one of S-ethyl trifluorothioacetate, S-cyanomethyl-S-dodecyl trithiocarbonate, 2-cyano-2-propyldodecyl trithiocarbonate, S,S-dibenzyl trithiocarbonate and dimethyl trithiocarbonate. The betaine-type surfactant is at least one of octanoyl thiobetaine, 3-[N,N-dimethyl,N-octadecyl]ammonium, 2-hydroxypropanesulfonate, tetradecyl sulfobetaine or lauryl dimethyl sulfobetaine; The heat stabilizer is at least one of thiourea, N-phenylthiourea, S-phenylthiophenyl sulfone, propylene thiourea, 4-methylaminothiourea or N,N′-dibutylthiourea. The anti-crosslinking agent is at least one of sodium formate, ascorbic acid, or isopropanol; The pore-forming agent is at least one of ammonium bicarbonate, sodium bicarbonate, or potassium bicarbonate. (2) A composite initiator is added to the mixed solution to initiate the reaction, and the polymerization product is obtained after the reaction; (3) Add hydrolysant and dispersant to the polymerization product and stir to mix. After hydrolysis, the comb-shaped amphoteric oil displacement agent is obtained. The amount of hydrolysant added accounts for 5.2-7.3% of the mass of the polymerization product, and the amount of dispersant added accounts for 0.4-0.6% of the mass of the polymerization product.

2. The preparation method according to claim 1, characterized in that, The preparation method of the zwitterionic surfactant is as follows: (11) Diethylaminoethyl methacrylate, 11-bromo-1-undecanol and stabilizer are added to an organic solvent, mixed well, and then a catalyst is added. The reaction is heated and the reaction product is obtained. (12) The reaction product and 2-mercapto-3-pyridinecarboxylic acid were added to water and mixed well. Then a catalyst was added and the reaction was heated to obtain the zwitterionic surfactant.

3. The preparation method according to claim 2, characterized in that, In step (11), the reaction temperature is 45-48℃ and the time is 13-16h; In step (12), the reaction temperature is 55-58℃ and the time is 20-23h.

4. The preparation method according to claim 2, characterized in that, The stabilizer is at least one of hydroquinone, p-tert-butylcatechol, p-hydroxyanisole, or diphenylamine. The catalyst is at least one of potassium iodide, ferric chloride, ferric bromide, copper chloride, or copper bromide.

5. The preparation method according to claim 2, characterized in that, In step (11), the mass percentages of each reactant are as follows: diethylaminoethyl methacrylate 15-18%, 11-bromo-1-undecanol 11-13%, organic solvent 68.4-73.7%, stabilizer 0.3-0.6%, and the amount of catalyst added in step (11) is 0.7-0.8% of the total mass of the reactants. In step (12), the mass percentage of each reaction raw material is as follows: reaction product 23-25%, 2-mercapto-3-pyridinecarboxylic acid 11.5-12.5%, deionized water 62.5-65.5%, and the amount of catalyst added in step (12) is 0.4-0.5% of the total mass of the reaction raw materials.

6. The preparation method according to claim 1, characterized in that, In step (2), the composite initiator includes a first reducing agent, a first initiator, a metal complexing agent, a second initiator, and a third initiator; Wherein, the first reducing agent is at least one of sodium metabisulfite, potassium metabisulfite, sodium thiosulfate, thiourea dioxide, zinc dithionite, or stannous chloride; the first initiator is at least one of lithium peroxide, potassium persulfate, zinc peroxide, ammonium persulfate, or cumene hydroperoxide; the metal complexing agent is at least one of ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, dihydroxyethylglycine, diethylenetriaminepentamethylphosphonic acid, or ethylenediaminetetramethylphosphonic acid; the second initiator is at least one of tert-butyl hydroperoxide, dicumene peroxide, or tert-butyl cumene hydroperoxide; and the third initiator is at least one of azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline hydrochloride, 4,4'-azodiphenyl ether, diisopropyl azodicarboxylate, and dibenzyl azodicarboxylate.

7. The preparation method according to claim 6, characterized in that, In step (2), the percentage of each raw material added to the mixed solution in the composite initiator is as follows: first reducing agent 0.0013-0.0015%, first initiator 0.0011-0.0012%, metal complexing agent 0.015-0.017%, second initiator 0.0075-0.0079%, and third initiator 0.011-0.012%.

8. The preparation method according to claim 1, characterized in that, In step (3), the hydrolysant is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or ammonia, and the dispersant is at least one of Span80, Span85, Span60 or Span40.

9. The preparation method according to claim 1, characterized in that, In step (2), the initiation temperature of the reaction is 9-11℃, the reaction temperature is 78-81℃, and the reaction time is 11-13h; and / or In step (3), the hydrolysis temperature is 78-81℃ and the time is 6-7h.

10. The preparation method according to claim 1, characterized in that, In step (2), before adding the composite initiator to initiate the reaction, a step of purging nitrogen into the reaction system to remove oxygen is also included; In step (2), after the reaction is complete, the reaction products are washed and granulated in sequence. In step (3), after hydrolysis is completed, the hydrolysis products are dried and ground in sequence to obtain the comb-shaped zwitterionic oil displacement agent.

11. A comb-shaped amphoteric oil displacement agent, characterized in that, It is prepared by any one of the preparation methods according to claims 1 to 10.

Citation Information

Patent Citations

  • Tackifier for drilling fluid and preparation method thereof

    CN114805678A

  • Fracturing fluid based on modified polyacrylamide and preparation method thereof

    CN117050742A